Community Participation and the Enhancement of the Roman Thermae of St Thomas, Mesolongi. (February 2013) - Poulimenou, Evgenia G
Abstract : This paper examines the process of enhancing an archaeological site and rendering it accessible to the wider public within a very tight time schedule, and will contemplate the role of the local community in this process. Focusing on the case study of the Roman Thermae of St Thomas (Agios Thomas) near Mesolongi, Western Greece, the various challenges and problems encountered during the excavation, partial restoration, and enhancement of the site (funded by the INTERREG II cross-border program of the 2nd Community Support Framework) will be addressed. Issues of community participation will be highlighted through the crucial involvement of the local people in the project and with a reflective outlook on the way heritage management is operating in Greece.